Expression analysis of genes encoding malectin-like domain (MLD)- and leucine-rich repeat (LRR)- containing proteins in Arabidopsis thaliana. Issue 1 (2nd January 2020) - Sultana, Mst Momtaz; Hachiya, Takushi; Dutta, Amit Kumar; Nishimura, Kohji; Suzuki, Takamasa; Tanaka, Ai; Nakagawa, Tsuyoshi
ABSTRACT: Malectin is a maltose-binding endoplasmic reticulum protein conserved in animals. In Arabidopsis thaliana, we identified four genes that encode malectin-like domain (MLD)- and leucine-rich repeat (LRR)-containing proteins (AtMLLRs): two were receptor-like proteins (AtMLLR1 and 2) and the other two were extracellular proteins (AtMLLR3 and 4). The promoter:G3GFP+promoter:GUS assay indicated the organ- and cell-specific expression of the AtMLLR2 and AtMLLR3 genes. Abbreviations: Cm r : chloramphenicol-resistance marker; G3GFP: G3 green fluorescent protein; GUS: β -glucuronidase; KD: kinase domain; LRR: leucine-rich repeat; MLD: malectin-like domain; RLK: receptor-like kinase; SP: signal peptide; TMD: transmembrane domain; Tnos: nopaline synthase terminator